2014
DOI: 10.1177/0956797613515681
|View full text |Cite
|
Sign up to set email alerts
|

The Scent of Disease

Abstract: Observational studies have suggested that with time, some diseases result in a characteristic odor emanating from different sources on the body of a sick individual. Evolutionarily, however, it would be more advantageous if the innate immune response were detectable by healthy individuals as a first line of defense against infection by various pathogens, to optimize avoidance of contagion. We activated the innate immune system in healthy individuals by injecting them with endotoxin (lipopolysaccharide). Within… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
139
3
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 243 publications
(151 citation statements)
references
References 25 publications
8
139
3
1
Order By: Relevance
“…First, a particular odor, such as fear odor, is assumed to have a distinctive signature, in the sense that it is comprised of distinctive chemical compounds, similar to what other researchers have demonstrated for gender [74], individuals [74] and disease [19]. Arguably, specific odor compounds related to fear may have become associated with particular situations in which they naturally occur (e.g., fear-inducing contexts such as academic examinations).…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…First, a particular odor, such as fear odor, is assumed to have a distinctive signature, in the sense that it is comprised of distinctive chemical compounds, similar to what other researchers have demonstrated for gender [74], individuals [74] and disease [19]. Arguably, specific odor compounds related to fear may have become associated with particular situations in which they naturally occur (e.g., fear-inducing contexts such as academic examinations).…”
Section: Discussionmentioning
confidence: 90%
“…Recent evidence provided strong biochemical support for the hypothesis that the odor produced by people who were sick was qualitatively different from a placebo condition, ostensibly refuting the argument that a person’s reaction to sweat produced under particular conditions is simply based on the presence of “more of the same components” [19]. Similar to what has been demonstrated for the scent of disease [19], a qualitatively different odor may be produced rather quickly in the case of fear, facilitated by apocrine sweat that arrives on the skin along with odorless precursor molecules. Enzymes of axillary (armpit) skin bacteria transform these precursor molecules into volatile odoriferous substances [20] that can be sampled with a sniff.…”
Section: Introductionmentioning
confidence: 99%
“…It has recently been demonstrated that odors are involved in social communication between humans where tentative evidence suggests that body odors communicate the age and health status of an individual to others12, as well as emotional state345, thus highlighting the social relevance of chemosignals. Moreover, most social interactions involve the act of drinking or eating where an impaired sense of smell will severely impair one’s experience given that smell is a principal component of the flavor percept when tasting food and drinks6 and an olfactory impairment will severely limit one’s ability to detect rotten or spoiled food7.…”
mentioning
confidence: 99%
“…Factors influencing sweat chemistry include gender (Penn et al, 2007), age (Yamazaki, Hoshino, & Kusuhara, 2010), genetics (Kuhn & Natsch, 2009;Martin et al, 2010), disease (Olsson et al, 2014), diet (Havlicek & Lenochova, 2006), physical activity (Callewaert et al, 2014a), and the bacterial species composition of the skin microbiome (Leyden, McGinley, Hölzle, Labows, & Kligman, 1981).…”
Section: The Production and Perception Of Body Odormentioning
confidence: 99%